TEACHING METHODS ACCORDING TO THE STAGES OF KOREAN PRONUNCIATION EDUCATION - Kyung Ae Kim (Bright Mind Publishing, 2025)
In teaching Korean as a foreign language, pronunciation instruction is the most important aspect of speaking and listening education. No matter how accurately a learner uses Korean grammar or expresses themselves with appropriate vocabulary, if they speak with incorrect pronunciation, their intended meaning may not be properly conveyed to the listener, potentially causing major misunderstandings in communication. As such, pronunciation plays a crucial role in communication, and in Korean language education, pronunciation instruction can be considered the foundation of teaching Korean. Similar to the process of language acquisition, in foreign language learning, pronunciation tends to become fixed in the early stages. Therefore, if pronunciation is not properly taught early on, it becomes difficult to correct later. This paper presents teaching methods according to the stages of Korean pronunciation education, along with specific types of pronunciation training activities.
Keywords: Korean, Korean language education, standard pronunciation, pronunciation education, pronunciation errors, pronunciation teaching methods, pronunciation assessment.